Verification of critical band hypothesis to explain the discrepancy in the amounts of TTS produced by noise and tones when presented at equal intensity and for equal duration - MN, Vyasamurthy; Ghanshyam Bishnoi Premalatha; Myihili (Journal of All India Institute of Speech and Hearing, 1973)
Pure-tones are assumed to be more dangerous than Octave-bands of noise (Anonymous, 1956). This was explained on the basis of critical-band hypothesis that stated that if a given amount of energy were concentrated within a single critical band, it would be more dangerous than if it were spread over several critical bands, e.g. over an octave (Kxyter, 1950). This critical band hypothesis is found not to be pertinent in explaining the different amounts of TTS (temporary threshold shift) produced by pure-tones and noise of same intensity level. (Ward, 1963). However an alternate hypothesis has been reported. Acoustic reflex is responsible for the difference in the amounts of TTS produced by octavebands of noise and pure tones, below 2KHz, of same intensity. The action of middle ear muscles differs for noise and pure-tone stimuli. In the case of puretones, the muscles after an initial contraction rapidly relax and hence more energy reaches the cochlea and consequently TTS will be more, whereas noise produces a more sustained reaction (there will be continuous re-arousal of the reflex of the middle ear muscles, probably because of the random nature of the noise), thereby TTS will be less as the energy reaching the cochlea will be less.